(3MOGFb GdCRGgQ aj eSJMSf GdCLhHI hGdeVMcGJ hGdMce hGdCeKGd hGdMcGjGJ hGdfhGOQs - (3CHh HcQ eMeO Hf eMeO Hf YGUe GdCfOdSj GdZQfGWj,J (B829 (3g` s
(3ChdgG (B:s
(3Cf CYdec KdGK NUGd, hGMOI hCfG aj jOc, hGdKGfjI hCfG Ydi GdTLQI, hGdKGdKI hCfG Ydi GdLHd bGd gGJ bGdJ(B: (3dG Jdgaf Ydi TF aGJ aNdi SHjdgG adeG UGQJ Ydi GdTLQI s
(3BNQgG (B:s
(3hEfj dCNaj eG djS NGajG hCcJe hLOG eKdg djS jcJe s
(3bWYI UZjQI ef fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B274s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B256 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdCOHs